Political and economic crises and their repercussions on the visual arts in the Kurdistan Region from the artists' perspective - ئەحمەد, د . دارا ئەوڕەحمان (Sulaimani Journal for Humanities, 2026)
To understand the political and economic crisis and its impact on painting in the Kurdistan Region from the artists' perspective. The descriptive approach was used to complete the research, according to the research topic and its objective, and the research sample consisted of artists in the city of Sulaymaniyah, in the Kurdistan Region of Iraq. The researcher then investigated the political and economic crises and their repercussions on the visual arts in the Kurdistan Region according to scientific steps., then the researcher identified the obstacles and found a solid solution for them due to the scientific steps. The researcher prepared the scale according to the approved scientific steps, and it consisted of (6) main paragraphs and (16) secondary paragraphs. After extracting its apparent validity and stability by re-applying the scores at two different times, using the (Pearson) correlation equation, which has a value between (0.25-0.50). After applying it to the research sample, through statistical procedures, the research results were obtained and the weighted average for all paragraphs was (1.68) the level is low. In the light of this result, there are This level indicates that artists are suffering from a severe financial and political crisis. The study is ended with some proposals and recommendations.
Keywords: Political; economic; crises; repercussions; visual arts Kurdistan Region; artists perspective